2008
DOI: 10.1093/geront/48.2.251
|View full text |Cite
|
Sign up to set email alerts
|

A Physical Activity Program to Mobilize Older People: A Practical and Sustainable Approach

Abstract: This practical program is potentially effective and sustainable with respect to mobilizing physically inactive older people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 46 publications
3
50
0
3
Order By: Relevance
“…Having a partner or friends who were physically active was significantly associated with physical activity. Jancey et al (2008) concluded that the opportunity for elders to be physically active with their neighbours was attractive and motivating, and led to the development of social networks. This was also found by Ståhl et al (2008), where the elders during research circle discussions recognized the importance of doing things together with others and having a natural meeting place within their district.…”
Section: Factors Affecting Walking Behaviour Among Older Adults In Thmentioning
confidence: 99%
See 1 more Smart Citation
“…Having a partner or friends who were physically active was significantly associated with physical activity. Jancey et al (2008) concluded that the opportunity for elders to be physically active with their neighbours was attractive and motivating, and led to the development of social networks. This was also found by Ståhl et al (2008), where the elders during research circle discussions recognized the importance of doing things together with others and having a natural meeting place within their district.…”
Section: Factors Affecting Walking Behaviour Among Older Adults In Thmentioning
confidence: 99%
“…Information about public activities can be an important measure to increase walking among elders [also found in Jancey et al (2008)] because it may reduce barriers related to the lack of a walking companion (Stathi et al 2012). Some elders highlight that exercise is about mental health, which can be related to well-being and elders' welfare, hence stimulating the need dimension.…”
Section: How Measures Relate To the Three Dimensions Of Walkingmentioning
confidence: 99%
“…The Perth Active Living Seniors (PALS) project was a prospective community-based PA program targeting older adults (Jancey et al, 2008). To be eligible, participants were required to be aged 65 to 74 years and healthy to the extent that participation in a low-stress walking program would not place them at risk for or exacerbate any existing health condition.…”
Section: Longitudinal Physical Activity Interventionmentioning
confidence: 99%
“…Program evaluation in health promotion is a complex process as it aims to gather evidence to assess the effectiveness of strategies and programs, maintain a level of accountability [16] and improve health promotion practice [17]. Despite impact and outcome evaluation being the most commonly reported forms of evaluation for randomised controlled trials, process evaluation, which is under reported, is vital as it accounts for factors that contribute to the success or failure of programs [18,19].…”
Section: Introductionmentioning
confidence: 99%